The Influence of Discipline and Job Satisfaction on Employee Performance (A Study in Baleendah Sub-district Bandung Regency) - Yuyun Wahyu Setiaji; S. Ridwan; R. Jusdijachlan (Greenation Publisher & Yayasan Global Research National, 2023)
A decrease in work discipline will have an impact on performance. Every company or organization must be able to improve work discipline in employees so that company goals can be achieved with greater profits. In addition to work discipline, low employee performance is influenced by low employee job satisfaction. In other words, low employee job satisfaction results in employees feeling less satisfied with their work. Based on preliminary observations, some employees at the Baleendah Sub-District Office expressed dissatisfaction with their work, for example related to payment where employees felt that the payment given was not proportional to the work done. In the preparation of this thesis, the author uses descriptive-veriative method research. The samples taken in this study were 30 employees at the Baleendah District Office. From the results of descriptive analysis, it is known that discipline and job satisfaction affect employee performance at the Baleendah District office, Bandung Regency simultaneously and partially.